Dislocation Engineered PtPdMo Alloy With Enhanced Antioxidant Activity for Intestinal Injury - Long, Wei; Mu, Xiaoyu; Wang, Jun-Ying; Xu, Fujuan; Yang, Jiang; Wang, Jingya; Sun, Si; Chen, Jing; Sun, Yuan-Ming; Wang, Hao; Zhang, Xiao-Dong (Frontiers in Chemistry, 2019)
Radiotherapy is the mainstay for abdomen and pelvis cancers treatment. However, high energy ray would inflict gastrointestinal (GI) system and adversely disrupt the treatment. The anti-oxidative agents provide a potential route for protecting body from radiation-induced injuries. Herein, highly catalytic nanocubes with dislocation structure are developed for treatment of intestinal injury. Structural and catalytic properties show that Mo incorporation can enhance antioxidant activity by dislocation structure in the alloy. In vitro studies showed that PtPdMo improved cell survival by scavenging radiation-induced ROS accumulation. Furthermore, after animals were exposed to lethal dose of radiation, the survival was increased by 50 % with the PtPdMo treatment. Radioprotection mechanism revealed that PtPdMo alleviated the oxidative stress in multi-organs especially the small intestine by inhibiting intestinal epithelium apoptosis, reducing DNA strands breaks and enhancing repairing ability. In addition, PtPdMo protected hematopoietic system by improving the number of bone marrow and peripheral blood cells.